The Reexamination of Geographic Earnings Conservatism - Kim, Myung-In (Archives of Business Research, 2022)
U.S. Multinational corporations are operated in many different countries. Their foreign and domestic earnings are separately reported in the annual report. This paper examined the difference between domestic and foreign earnings in terms of conservatism using a variety of model specifications for conservatism. I found that the degrees of conservatism of domestic earnings are much higher than foreign earnings in all the model specifications for conservatism, which is in line with prior literature (Hwang and Kim 2022). More importantly, I found that the higher financial leverage, the declining asset growth and the higher information asymmetry significantly increase the level of conservatism of domestic earnings rather than foreign earnings.